Incrementar la pena de la privación de la libertad al delito de contrabando para combatir la evasión de la obligación tributaria aduanera - Castillo Eras, Pedro Daniel (2016)
The importance and transcendence of the partner-juridical problem of "Incrementing the grief of the privation of freedom to the crime illegally to combat the tributary custom evasion", it is based mainly in the necessity of helping to the administration of justice, and of contributing with the support of the organs of control customs officer and social control to prevent the smuggling of goods for the border areas that it is evidenced by the national and local news to newspaper. When investigating this topic, we find serious problems in the eradication of the smuggling, because the offenders receive sanctions of until five years of prison that it doesn't provide affect some, for their rehabilitation, inclusive in some trials it doesn't end up being dictated it sentences condemnatory. The theoretical work and of field of the present thesis it allowed me to obtain approaches, with clear and precise foundations, of very grateful bibliography that you/they contributed to the verification of objectives, and contrastación of the outlined hypotheses, allowing to support the proposed changes. The content of the thesis is the author's intellectual effort in the scientific and methodological environment that approaches theoretical and empirically, the vulneración of the patrimony of the State, when not paying the taxpayer its tributes in the escape of merchandises for the Ecuadorian frontiers.